The Correlation Between English Language Learning Strategies and Students' Thinking Style at The Second Grade of MAN 1 Kolaka - Ray Suryadi; Syamsinar Syamsinar; Indrayani Simpuruh; Firdayana Firdayana (Fakultas Sastra - Universitas Muslim Indonesia, 2022)
This study was conducted at MAN 1 Kolaka. The objective is to find out information and data weather there is any correlation between English language learning strategy and students’ thinking style at the second grade AGAMA I of MAN 1 Kolaka. The research design is descriptive quantitative in nature. The data were collected through questionnaires. Findings revealed that the English Language Learning Strategy at the second grade AGAMA I of MAN 1 Kolaka were Metacognitive with the total frequency of 47% and Students’ Thinking Style were Extrovert with the total percentage of 53%. The Population of the study was the second-grade students of MAN 1 Kolaka and the sample of the research was 1 class based on random sampling technique which consisted of 15 students. The data analysis used in this research was product moment formula which showed that there were no correlation between English Language Learning Strategy and Students’ Thinking Style. It could be synthesized that hypothesis were r-count was lower than r-table. So H1 was rejected and H2 was accepted. The coefficient Correlation between English Language Learning Strategies and Students’ Thinking Style did not have any significant correlation with the r-count = -0,218 was lower than r-table 0,514 at the significance level 5% and degree of freedom (df) was 15 (-0,218>0,514). Therefore, it was categorized as low correlation. H0 and H1 was rejected and H2 was accepted.